Performance Improvement through Signal Optimization: A Case Study of Ekantakuna Intersection - Shrestha, Riti; Nyachhon, Umanga Man; Shrestha, Samyak; Maharjan, Rahul; Amatya, Sabil Lal (International Journal on Engineering Technology, 2026)
Traffic congestion has long been one of the most persistent challenges in Kathmandu Valley. Intersections have emerged to be a primary factor contributing to this problem where congestion largely undermines efficiency in daily travel. This study focuses on assessing the present operational conditions at critical junction in the ring road, namely Ekantakuna and exploring measures to improve performance at intersection using SIDRA 8.0. Video graphic survey was conducted for 3 consecutive weekdays. To determine peak traffic periods, a 12-hour volume count was extracted from one day of the data, establishing peak ranges for both morning and evening. From this analysis, volume count within the range was carried out for remaining days and maximum peak hour from the three days was taken for the study. Data collected from the Peak hour which includes; Traffic volume, Back of Queue, Saturation flow etc. were applied for the formulation of model to assess the present condition of intersection and recommend different improvement measures. The current operational performance at Ekantakuna showed an average delay of 72.7 seconds and Level of Service (LOS) of E. Two alternatives were approached among which, Alternative 1 targeted Signal Optimization, reducing average vehicular delay from 72.7 seconds to 53.6 seconds and improving LOS to D. Similarly, Grade-Separated intersection was introduced in Alternative 2, it further reduced Average delay from 72.7 seconds to 40.1 seconds while maintaining an improved LOS of D. The findings from the study conclude that targeted model-based optimization can substantially enhance the operational performance of intersection.